Shockheaded Peter and other songs from the Tiger Lillies live concert in new York - Jacques, Martyn 1959- (Kultur, 2006)
"Impossible to categorize, the Tiger Lillies have been singing their own brand of blasphemous ballads, tragic tales and debauched ditties since 1991. The band fuse the spirit of punk with the passion of chanson, while at the same time evoking the disturbing and forgotten music of our dim and distant past such as religious masses, Bavarian folk music, Berlin cabaret and Victorian English music hall song. This concert from the PS122 theater in New York features a selection of songs, including some from their sensational smash-hit theater production Shockheaded Peter"--container